2012
DOI: 10.1080/19440049.2011.652196
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation and validation of a quantitative and confirmatory method for residues of macrolide antibiotics and lincomycin in kidney by liquid chromatography coupled to mass spectrometry

Abstract: A solid phase extraction followed by a liquid chromatography (LC)-tandem mass spectrometry (MS/MS) detection method for the confirmatory analysis of lincomycin (LIN), clindamycin (CLI), tilmicosin (TIM), erythromycin (ERI) and tylosin (TYL) residues in kidney were optimised and validated for monitoring and controlling the use of these antibiotics in food producing-animals. The method optimisation was carried out by testing changes in the extraction buffer pH and in the ammonium/acetonitrile concentrations on S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The NRCP is an attribution of Ministry of Agriculture, Livestock and Food Supply (MAPA) [9,10]. Many studies have reported methodologies based on liquid chromatography couple to mass spectrometry in single or tandem mode (LC-MS and LC-MS/MS, respectively) to determine macrolides and lincosamides residues in milk [11][12][13][14] and muscle [15][16][17][18][19][20][21], and also in different matrices, such as honey [22,23], eggs [24], fish [25] and kidney [26,27]. These compounds are routinely included in multiresidue methodologies [14,16,19,[22][23][24][28][29][30][31], and there is minor publications of macrolides class only [32,33] or macrolides and lincosamides only [21].…”
Section: Introductionmentioning
confidence: 99%
“…The NRCP is an attribution of Ministry of Agriculture, Livestock and Food Supply (MAPA) [9,10]. Many studies have reported methodologies based on liquid chromatography couple to mass spectrometry in single or tandem mode (LC-MS and LC-MS/MS, respectively) to determine macrolides and lincosamides residues in milk [11][12][13][14] and muscle [15][16][17][18][19][20][21], and also in different matrices, such as honey [22,23], eggs [24], fish [25] and kidney [26,27]. These compounds are routinely included in multiresidue methodologies [14,16,19,[22][23][24][28][29][30][31], and there is minor publications of macrolides class only [32,33] or macrolides and lincosamides only [21].…”
Section: Introductionmentioning
confidence: 99%